African Irregular Migrants in Malta: Exploring Perceptions and Renegotiating the Socio-Cultural Siege of Malta - Hannah E Durick (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
This paper discusses the influx of African irregular migrants seeking asylum in Malta and how their arrival and growing presence in Malta is perceived by the Maltese. Since becoming an EU Member State in 2004 Malta has been overwhelmed by the number of irregular migrants arriving on its shores while en route to continental Europe. Due to its proximity to the North African coastline Malta becomes a frequent, albeit unintentional, destination for African migrants who are rescued in Maltese waters and subsequently placed in a closed detention facility until their legal status is determined in a court of law. Although it is simultaneously the smallest and most densely populated country in Europe, Malta is obligated to abide by the 2003 Dublin II Regulation, which places a disproportionately large burden on Malta—a small island nation with significant spatial and resource limitations. The international community’s criticism of Malta’s neglect and mismanagement of its humanitarian crisis, however, are not unwarranted. Social sanctums and domestic legal policies regarding how Malta’s irregular migrant population should be perceived and handled remain diametrically opposed and socio-economic, cultural and racial tensions between irregular migrants and Maltese citizens run high. Based on fieldwork conducted in Malta in 2011, this paper examines the problem of irregular migration in Malta and how existing Maltese perceptions are shaping some of the domestic policies that have been internationally criticized.
Keywords: Migrants; Malta